1993
DOI: 10.1128/mcb.13.4.2377
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ornithine decarboxylase: exposure of the C-terminal target by a polyamine-inducible inhibitory protein.

Abstract: Polyamine-mediated degradation of vertebrate ornithine decarboxylase (ODC) is associated with the production of antizyme, a reversible tightly binding protein inhibitor of ODC activity. The interaction of antizyme with a binding element near the N terminus of ODC is essential but not sufficient for regulation of the enzyme by polyamines (X. Li and P. Coffino, Mol. Cell. Biol. 12:3556-2562, 1992. We now show that a second element present at the C terminus is required for the degradation process. Antizyme caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 43 publications
7
146
0
1
Order By: Relevance
“…Rat ODC contains two PEST regions (20) in an internal region and near the carboxyl-terminal, respectively. The carboxyl-terminal region of ODC (422-461) including the second PEST region (423-449) has been assigned as an element necessary for the rapid degradation of ODC (6). Antizyme inhibitor lacks this region and does not contain PEST sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat ODC contains two PEST regions (20) in an internal region and near the carboxyl-terminal, respectively. The carboxyl-terminal region of ODC (422-461) including the second PEST region (423-449) has been assigned as an element necessary for the rapid degradation of ODC (6). Antizyme inhibitor lacks this region and does not contain PEST sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The turnover of ODC is very rapid and highly regulated (3,4). The degradation of ODC catalyzed by the 26 S proteasome is accelerated by ODC antizyme (5,6), an inhibitory protein induced by polyamines (7). Strict regulation of ODC appears to be important for cell growth, because overproduction of ODC is associated with neoplastic transformation (8,9), whereas overproduction of antizyme inhibits cell growth (10,11).…”
mentioning
confidence: 99%
“…If antizyme does have a direct affinity for the polyamine transporter as well as ODC, then it would appear that the dynamics of this partitioning of a labile regulatory protein (antizyme) between interactions with a stable membrane protein (transporter) and a labile cytoplasmic enzyme (ODC) would be quite complex. Further, the binding of antizyme to ODC is thought to alter the structure of ODC sufficiently to expose a region near the C-terminal end that stimulates degraReceived 30 December 1993/28 January 1994; accepted 28 January 1994 dation by the 26 S proteasome [10,11,29]. If antizyme also binds a component of the polyamine transporter, then it will be of interest to ascertain whether this interaction has any effect on the half-life of this protein that has previously been shown to be rather stable [17].…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid residues R 131 and G 145 of Az1 are essential for the degradation of Aurora-A It has been demonstrated that N terminus of ODC interacts with Az1 (Li and Coffino, 1993) and that the element contained within amino acids 130-145 of rat Az1 is essential for targeting ODC for proteasomal degradation (Chen et al, 2002). To define whether this targeting domain of Az1 is involved in the targeting of Aurora-A for degradation, Az1 mutant, which lacks the N-terminal 120 amino acids (DN120-Az1) and Az1, which lacks only the amino acids 130-145 (D130-145-Az1) (Figure 4a), were made and used to study in vivo degradation of Aurora-A in HeLa cells as described earlier.…”
Section: Az1 Interacts With Aurora-a In Vivomentioning
confidence: 99%
“…Az increases ODC degradation by enhancing ODC association with proteasome, rather than accelerating the rate of proteasomal processing (Zhang et al, 2003). The attachment of Az causes conformational changes in ODC, thereby exposing its C-terminal degradation signal for recognition by 26S proteasome (Li and Coffino, 1993). Unlike Ub, Az is usually spared from destruction and released from the ODCAz complex at the proteasome (Murakami et al, 1992).…”
Section: Introductionmentioning
confidence: 99%